Coronavirus (CoV) proteins (version 2020.4) in the IUPHAR/BPS Guide to Pharmacology Database - Alexander, Stephen P.H.; Ball, Jonathan K.; Tsoleridis, Theocharis (IUPHAR/BPS Guide to Pharmacology CITE, 2020)
Coronaviruses are large, often spherical, enveloped, single-stranded positive-sense RNA viruses, ranging in size from 80-220 nm. They can cause diseases ranging from the common cold to severe acute respiratory syndrome (SARS).